Inclusion evolution after calcium addition in Al-killed steel with different sulphur content. (28th May 2018) - Zhang, T.; Liu, C.; Mu, H.; Li, Y.; Jiang, M.
ABSTRACT: The inclusion evolutions after calcium treatment in Al-killed steel with different sulphur content were determined by chemical experiments and thermodynamics calculations. The results show that the inclusions are calcium aluminate with a little amount of calcium sulphide in low content sulphur steel after calcium treatment. As the sulphur content in steel increases, the typical inclusions generated in steel are layered or homogeneous irregular oxysulphides. A number of pure sulphides can be observed in higher content sulphur steel, and the morphology of sulphides with different CaS/MnS mass ratio has different shape. Thermodynamics calculations of Al–Ca–O–S–Mn system inclusions in steel at 1873 K and during solidification process were comprehensively conducted, considering all types of inclusions. The experimental results are in good agreement with thermodynamic calculations, which can predict the formation of the inclusions in Al-killed steel with different sulphur content.